(untitled) (LSP International Journal, 2020)
In the field of lexical semantics, synonym is one of the aspect that can classify some words that brings a same meaning. However, as a result of changing times and technology, some lexical generally has specific synonyms meaning-making as classified in lexicography also can have addition or abortion of the lexical equivalent. Therefore, this study, fully in qualitative form, was performed by applying text anylisis based on corpus data such as Pangkalan Data Korpus Dewan Bahasa dan Pustaka and Facebook. This study has analyzed the meaning-making for the synonym of “nepotism” based on the corpus data. In lexicography terms, lexical “nepotism” has a synonym meaning with lexical “cronyism” as both of these lexicals refer “an act or policy that concern or exaggerate their own relatives and friends” and “a policy that puts priority or concern more to their closed friends in the inauguration of a ministry, giving a project and others.” This synonym meaning-making has been applied into an authoritative theory of Bridging Cross Reference (BCR) by Kempson (1986) and Relevance Theory (RT) by Sperber and Wilson (1986; 1995). This make the meaning-making for the synonym lexical can be answered with high reliability. In conclusion, the findings of this study shows lexical ‘kabel’ or ‘cable’ is an additional synonym lexical with lexical ‘nepotism’ and ‘cronyism.’